Penerapan ADR dan Potensi Arbitrase dalam Penyelesaian Sengketa Medis di Indonesia - Anggraeni, Happy Yulia; Sagita, Praniko Imam; Yusmana, Fane Virginia; Reza, Muhamad; Sehafudin, Sultan; Johan, Willy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Medical disputes in Indonesia often face challenges such as lengthy litigation processes, high costs, and low satisfaction among the parties involved. In this context, Alternative Dispute Resolution (ADR), particularly mediation and arbitration, offers a more efficient solution. Mediation has been regulated under Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution as well as Supreme Court Regulation (Perma) No. 1 of 2016. However, arbitration mechanisms still lack a specific legal framework, even though Law No. 17 of 2023 on Health emphasizes the importance of swift and fair dispute resolution in healthcare services. Unlike litigation, arbitration allows for final, expedited, and binding resolutions. Countries such as the United States, the United Kingdom, and Taiwan have successfully implemented arbitration in medical disputes. Taiwan, for instance, has specific regulations that facilitate medical arbitration processes, providing legal certainty for patients and healthcare providers. Indonesia can learn from these international experiences. By clarifying arbitration regulations in the healthcare sector, the government can strengthen a dispute resolution system that is responsive to societal needs. This enhancement can be achieved through the training of professional arbitrators and promoting the use of ADR, ensuring that medical disputes are resolved more fairly, quickly, and cost-effectively.